2019
DOI: 10.2174/1389201020666190311143554
|View full text |Cite
|
Sign up to set email alerts
|

Combined Amelioration of Ginsenoside (Rg1, Rb1, and Rg3)-enriched Korean Red Ginseng and Probiotic Lactobacillus on Non-alcoholic Fatty Liver Disease

Abstract: Background: Red ginseng is a traditional medicine that has been used to treat numerous metabolic and inflammatory diseases. Probiotic administration has been established to have beneficial effects in non-alcoholic fatty liver disease (NAFLD). The purpose of this study was to determine whether a combination of Korean red ginseng (KRG) and probiotics could synergistically reduce NAFLD and liver inflammation compared with the effects reported for each individual product. Method: db/db and C57BL/6 mice were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…For example, Lingguizhugan decoction and calorierestriction therapy together could enhance the reduction of fasting blood lipid levels (Yuanyuan et al, 2015;Cao et al, 2016). The combination of Korean red ginseng and probiotic L a c t o b a c i l l u s s y n e r g i s t i c a l l y a m e l i o r a t e d h e p a t i c inflammation (Kim et al, 2019a). The combination of Ganmaidazao and Shengmai-Yin decoction is applied as adjuvant therapy for Type II diabetes mellitus via activation of HSL, PPARa, and AMPK/PI3K/AKT, and inhibition of SREBP-1/FAS, influencing insulin sensitivity, and lipid biosynthesis (Li et al, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, Lingguizhugan decoction and calorierestriction therapy together could enhance the reduction of fasting blood lipid levels (Yuanyuan et al, 2015;Cao et al, 2016). The combination of Korean red ginseng and probiotic L a c t o b a c i l l u s s y n e r g i s t i c a l l y a m e l i o r a t e d h e p a t i c inflammation (Kim et al, 2019a). The combination of Ganmaidazao and Shengmai-Yin decoction is applied as adjuvant therapy for Type II diabetes mellitus via activation of HSL, PPARa, and AMPK/PI3K/AKT, and inhibition of SREBP-1/FAS, influencing insulin sensitivity, and lipid biosynthesis (Li et al, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some researches have demonstrated that some active components in JGXZ has obvious effects on decreasing lipid levels in NFALD. A study demonstrated that Rg1 and Rb1 were involved improving lipid levels and ameliorate in ammation in NAFLD mice [28]. Paeoni orin has obvious effects on suppressing lipid ectopic deposition, enhancing insulin sensitivities and decreasing oxidation in NAFLD rats [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…As an active ingredient derived from natural products, ginseng ginsenoside has excellent therapeutic effectiveness with high bioavailability and little biotoxicity, and has been widely employed to treat various metabolic syndromes such as diabetes, liver diseases, heart diseases, cancer, etc [ 20 , 21 , 22 , 23 , 24 ]. A mixture of ginsenoside Rg3, Rg1, Rb1, and probiotics has been used as a putative treatment for NAFLD symptoms to diminish liver inflammation by decreasing the expression of IL-1β and phospho-p38 [ 23 ]. Ginsenoside Rg1 exhibited an anti-inflammatory effect on palmitic acid-induced HepG2 cells via the AMPK/NFκB pathway [ 24 ].…”
Section: Introductionmentioning
confidence: 99%